(untitled) (Fiep Bulletin - online, 2014)
This present paper aims to describe family relationships from professional dancers who are openly gay, and graduated in Physical Education course. Firstly, it is shown how each one of these professionals relate to close family members – parents and siblings. Further, it is displayed connections between their life courses aiming to find similarities amongst them. It comes to a conclusion that mothers are believed to be a strong family reference for these professionals. The family demonstrates concerns towards their children’s financial stability due their career choices, and that there still have been a correlation between homosexuality and promiscuity from them.